2022
DOI: 10.1039/d2qi00421f
|View full text |Cite
|
Sign up to set email alerts
|

WVI–OH functionality on polyoxometalates for water reduction to molecular hydrogen

Abstract: When a polyoxometalate cluster surface is grafted with WVI–(OH)2 functionality, the surface-modified POM turns into an efficient & stable electrocatalyst for hydrogen evolution reaction by water reduction. We performed detailed kinetic studies for this electrocatalysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 59 publications
0
14
0
Order By: Relevance
“…Thus, compound 1 is stable up to 100 CV cycles in the HER catalytic action at neutral pH (Figure a), whereas it is durable enough for 500 CV cycles (Figure b) when subjected to multiple CV cycles in an aqueous acidic pH 3 electrolyte. As shown in Figure c,d, this CV cycling stability at operating pH values (at neutral pH and in acidic pH 3) is interpreted by the plots of specific current densities vs the number of CV cycles, where the specific current density data points have been collected as the last data of the catalytic HER current densities. The relevant observations highlight the fact that the stability of POMs increases while moving down to the lower pH solutions. Further, the chronoamperometry (CA) measurements were performed on compound 1 -coated carbon paper (CP) electrodes at the catalytic HER region of −1.1 V vs Ag/AgCl (3 M), and it is found that stable and steady-state cathodic current is maintained for a period of 2 and 6 h at neutral pH and in acidic pH 3, respectively, (Figure e,f) which is an almost equivalent timing to the cycling stability time for both the cases.…”
Section: Resultsmentioning
confidence: 87%
“…Thus, compound 1 is stable up to 100 CV cycles in the HER catalytic action at neutral pH (Figure a), whereas it is durable enough for 500 CV cycles (Figure b) when subjected to multiple CV cycles in an aqueous acidic pH 3 electrolyte. As shown in Figure c,d, this CV cycling stability at operating pH values (at neutral pH and in acidic pH 3) is interpreted by the plots of specific current densities vs the number of CV cycles, where the specific current density data points have been collected as the last data of the catalytic HER current densities. The relevant observations highlight the fact that the stability of POMs increases while moving down to the lower pH solutions. Further, the chronoamperometry (CA) measurements were performed on compound 1 -coated carbon paper (CP) electrodes at the catalytic HER region of −1.1 V vs Ag/AgCl (3 M), and it is found that stable and steady-state cathodic current is maintained for a period of 2 and 6 h at neutral pH and in acidic pH 3, respectively, (Figure e,f) which is an almost equivalent timing to the cycling stability time for both the cases.…”
Section: Resultsmentioning
confidence: 87%
“…In our very recent report, we have shown the catalytic HER activity by a tungsten POM cluster, which is synergistically activated by a redox-active copper wheel . We have also demonstrated that if a transition metal aqua species is confined in a constrained space or put on the POM cluster surface by a coordinate covalent bond, it drives electrocatalytic water oxidation. , Our other report has shown that if the −W­(OH) 2 moiety is grafted on a POM cluster surface, this moiety acts as a functional group for electrocatalytic water reduction to molecular hydrogen . These two important facts inspired us to explore a POM-based compound that has a W–OH moiety (referring to water reduction) and a −M­(H 2 O) n group (referring to electrocatalytic water oxidation) so that it would act as a bifunctional catalyst for HER as well as for OER.…”
Section: Introductionmentioning
confidence: 75%
“…34,35 Our other report has shown that if the −W(OH) 2 moiety is grafted on a POM cluster surface, this moiety acts as a functional group for electrocatalytic water reduction to molecular hydrogen. 39 These two important facts inspired us to explore a POM-based compound that has a W−OH moiety (referring to water reduction) and a −M(H 2 O) n group (referring to electrocatalytic water oxidation) so that it would act as a bifunctional catalyst for HER as well as for OER. Thus, in the present work, we have reported the synthesis and crystal structure of a three-dimensional-framework-containing polyoxometalate…”
Section: ■ Introductionmentioning
confidence: 99%
“…Polyanion 1 contains two tri-lacunary building blocks {β-SbW 9 O 33 }, three tungsten units of two {WO 2 (OH)} + and one {WO 2 } 2+ , and a {RuC 7 H 3 NO 4 } 2+ centre (Figure a). Based on the bond valence-sum (BVS) calculation, , the values of the O55 and O63 are 1.000 and 0.875, respectively (Table S2), indicating that these two oxygens linked to W are monoprotonated (Figure b), that is the W–OH groups. , Naturally, the intact details of bond distances and angles are given in the crystallographic tables (Tables S3 and S4). Three W atoms and one Ru atom in the linking groups form an irregular quadrilateral middle-banded structure and present at the sandwiched positions.…”
Section: Resultsmentioning
confidence: 99%